Tendances démographiques et impact économique - Sirard, André (Assurances, 1989)
Economic growth in most leading industrialized nations is quite strong. The surprising burst of growth we saw in most OECD countries in 1988 led lo a small acceleration in inflation and a round of interest rate increases. However, slower growth is expected over the next 12 months. Inflation will remain modest and interest rates will probably decline.